The Use of Poetry for Reading Skills of Chinese Language Education Study Program Students Universitas Negeri Malang - Lunmisay, Hanna Widi Krisjayanti; Ventivani, Aiga; Kurniawan, Deddy (Confucius Institute Universitas Sebelas Maret, 2025)
This research aims to describe the use of poetry for Reading Skills of Chinese Language Education Study Program Students at State University of Malang and describe student responses to the use of poetry book media. The learrning materials used from poetry of Song Dynasty 诉衷情 [sù zhōngqíng] and 卜算子 [bǔsuànzǐ]. This research using a descriptive qualitative approach. Research data sources from 34 students Chinese Language Education Study Program Students at State University of Malang cohort of 2023. Data Collection Techniques in this research using observation sheet and questionnaire. The results of this study indicate that the use of learning media “宋時三百首” [Sòngshīsān bǎi shǒu] Poetry Book is going well. Based on the results of the study, students felt helped and happy when using the book media. Although there were students who had difficulty understanding when using the poetry book, students stated that the learning media of the poetry book “宋時三百首” [Sòngshīsān bǎi shǒu] could help them to understand the poetry material given, in improving reading skills. This poetry book can also be used for further learning in other courses so that it can also help develop other skills such as listening, writing, and speaking.